194k views
1 vote
3x - 2y + 3z = 6

x + 3y - 3z = -14
-x + y + 5z = 22

whats the answer in pretenses for (x,y,z)

User Youngju
by
4.9k points

1 Answer

1 vote

Answer:

Point Form: ( − 2 , 0, 4 ) Equation Form: x = − 2 , y = 0 , z = 4

Explanation:

Solve for the first variable in one of the equations, then substitute the result into the other equation.

User SpongePablo
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.